ANALISIS PEMBERDAYAAN MASYARAKAT PESISIR DI PAGUYUBAN MITRA NELAYAN SEJAHTERA JUWANA KABUPATEN PATI - Ayu Novita Sari; Retna Hanani (Journal of Management and Public Policy, 2026)
Community empowerment in the Paguyuban Mitra Nelayan Sejahtera Juwana is an effort to accommodate fishermen who own purse seine vessels with a gross tonnage (GT) of more than 30. This study aims to analyse the empowerment of coastal communities, particularly fishermen who own purse seine vessels in the Paguyuban Mitra Nelayan Sejahtera Juwana, Kabupaten Pati. This study uses a qualitative descriptive method. The data sources in this study were obtained from interviews, observations, and documentation. The informant selection technique was carried out using purposive sampling. Data analysis was conducted using the empowerment theory perspective. The results of the study show that the empowerment of fishermen who own boats in the Paguyuban Mitra Nelayan Sejahtera Juwana has gone through three stages, including raising awareness among the fishing community of the problems or threats they face, enhancing the capacity of individual fishermen and fishing groups through discussion, education, knowledge transfer, and strengthening communication for policy advocacy that supports the sustainability of the fishing business, as well as increasing the empowerment of members in political, economic, and social aspects. The driving factors in the empowerment at the Paguyuban Mitra Nelayan Sejahtera Juwana are the motivation of members to join, the availability of sufficient funds from member contributions to cover operational costs, and the availability of adequate facilities and infrastructure. Meanwhile, the factors hindering empowerment activities are government policies in the form of laws, regulations, and directives from the central government that are not adaptive to the real conditions of fishermen who own boats.